INFLUENCE OF PLANT COMPONENTS ON IMPROVING THE QUALITY OF LOW-FAT CREAM - Рижкова, Таїсія; Гейда, Ірина (SWorldJournal, 2023)
The purpose of the article was to present the results of research obtained during the development of the technology of low-calorie sour cream of 10% fat from cow’s milk, enriched with whey decoctions of powders from the herbs althea, burdock root, and ech